PENGEMBANGAN KAPABILITAS KEINOVASIAN IKM BERBASIS PADA ORIENTASI KEWIRAUSAHAAN DAN PEMBELAJARAN ORGANISASIONAL - Rahab Rahab; Sudjono Sudjono (Asian Journal of Innovation and Entrepreneurship, 2012)
The purpose of this paper is to examine the nomological relations among market-orientation, entrepreneuship-orientation, learning-orientation and innovativeness in medium-sized business (SMEs). The study involves a questionnaire-based survey of owners from small-medium sized-firms operating in Purbalingga regency. A total of 150 usable questionnaires were received from SMEs. These were subjected to a Partial Least squares (PLS) analysis. The results show that firm learning-orientation and firm market-orientation positively influences firm innovativeness; firm market-orientation positively impacts firm learning orientation; firm learning-orientation mediates the relationship between firm market-orientation and firm innovativeness. This study has implications for SEMs aiming at increasing their innovativeness based on its orientation on market and organization learning. Keywords: SMEs, learning, entrepreneurship, market, innovativeness